FMRI in Bell's Palsy: Cortical Activation is Associated with Clinical Status in the Acute and Recovery Phases. Issue 1 (4th November 2020) - Calistri, Valentina; Mancini, Patrizia; Raz, Eytan; Nicastri, Maria; Tinelli, Emanuele; Russo, Francesca Yoshie; Fiorelli, Marco; De Seta, Elio; Carpentieri, Daniele; De Vincentiis, Marco; Caramia, Francesca
ABSTRACT: BACKGROUND AND PURPOSE: Using functional magnetic resonance imaging (fMRI), we explored cortical activation in patients with acute Bell's palsy (BP) and analyzed its correlates with clinical status in the acute phase, and with 6‐month outcome. METHODS: Twenty‐four right‐handed patients with acute BP within 15 days of onset and 24 healthy controls underwent fMRI during performance of unilateral active (hemi‐smiling) and passive lip movement tasks with both the paretic and the normal lip. The degree of paresis was evaluated during the acute stage and at the 6‐month follow up using the House‐Brackmann (HB) grading scale. Complete recovery was defined as HB grade II or less at the end of the 6‐month period. The difference in the HB grade (ΔHB) between the acute stage and the 6‐month follow up was used to evaluate clinical improvement. RESULTS: There were 24 patients with unilateral acute BP. HB grades ranged from III to VI. At 6 months, 11 patients (46%) had completely recovered and 12 (50%) were partially improved. Compared with healthy subjects, BP patients had a significantly greater activation of the frontal areas and the insula ipsilateral to the paretic side. In BP patients, there was an inverse correlation between the activation of the ipsilateral hemisphere when moving the paretic side and the degree of paresis at baseline. An association was also observed between activation and clinical outcome (both complete recovery and ΔHB). CONCLUSIONS: In patients with BP, fMRI may represent a useful tool to predict long‐term outcome, guide therapeutic approach, and monitor treatment response.